Macromolecular architectures of corannulene: synthesis, properties, and applications of polymers containing a molecular bowl of carbon - Stuparu, Mihaiela Corina (2023)
Corannulene (C20H10) is a bowl-shaped polycyclic aromatic hydrocarbon. The molecular curvature endows corannulene with a dipole moment, affinity for electrons, and the capacity to host fullerenes. Corannulene can also act as a guest in the cavity of gamma cyclodextrin. Corannulene is thus an appealing building block for polymer synthesis. It is envisaged that the multifaceted properties of corannulene can be combined with the modularity of synthetic polymers to access functional soft materials. Indeed, these efforts are now a decade old and some corannulene polymers have already been tested in real-life devices. In this perspective, we will contemplate the motivation behind these efforts, progress made within the past decade, and future prospects of the field.